Preliminary trials of the BioBaler working in Brazilian eucalypt plantations - Guerra, Saulo P. S. [UNESP]; Oguri, Guilherme [UNESP]; Denadai, Marcelo S. [UNESP]; Esperancini, Maura S. T. [UNESP]; Spinelli, Raffaele (Natl Inquiry Services Centre Pty Ltd, 2018)
The increasing demand for renewable energy feedstock has raised interest in growing eucalypts for fuel wood production, which is achieved by establishing very dense plantations cut every 18-24 months. The high moisture content of fresh Eucalyptus may handicap cut-and-chip operations, and offers a unique opportunity for supply chains based on baling. Therefore, the Canadian-made BioBaler was tested in Brazil on a eucalypt energy plantation, as well as on the resprouts generated by a conventional pulpwood plantation after severe frost damage. The BioBaler coped well with both crops, achieving high productivity levels: 7.1 and 3.3 t h(-1) in the energy plantation and the failed crop treatments, respectively. Harvesting cost was estimated at (sic)13 t(-1) and (sic)26 t(-1) for the energy plantation and the failed crop, respectively. Productivity and harvesting cost were comparable with those reported in previous studies conducted in other countries on similar crops. Productivity was directly proportional to field stocking. Future studies should test the machine on a wider range of work conditions and include bale extraction, storage, processing and transportation, in order to estimate an overall supply chain cost and allow direct comparison with alternative options.
Keywords: biomass; cost; efficiency; energy; productivity